Determination of the structure of a decay accelerating factor-binding clinical isolate of echovirus 11 allows mapping of mutants with altered receptor requirements for infection. - Stuart, A; McKee, T; Williams, P; Harley, C; Shen, S; Stuart, D; Brown, T; Lea, S (2002)
We have used X-ray crystallography to determine the structure of a decay accelerating factor (DAF)-binding, clinic-derived isolate of echovirus 11 (EV11-207). The structures of the capsid proteins closely resemble those of capsid proteins of other picornaviruses. The structure allows us to interpret a series of amino acid changes produced by passaging EV11-207 in different cell lines as highlighting the locations of multiple receptor-binding sites on the virion surface. We suggest that a DAF-binding site is located at the fivefold axes of the virion, while the binding site for a distinct but as yet unidentified receptor is located within the canyon surrounding the virion fivefold axes.